In situ quantitative diagnosis of insulated building walls using passive infrared thermography. Issue 1 (1st January 2022) - Larbi Youcef, M. H. A.; Feuillet, V.; Ibos, L.; Candau, Y.
ABSTRACT: The research project DPE-IITI aims to carry out the in situ diagnosis of energy performance of buildings by quantifying the insulation level of walls. The on site monitoring method is based on the use of passive infrared thermography, meteorological measurements (air temperatures, solar flux), thermal modelling and identification algorithm. A measurement campaign was conducted in a school in the city of Noisiel (suburb of Paris, France). Experimental results based on a radiometric model and finite element simulation parameter identification approach show the potential of the method to quantify the thermal insulation level of a building wall. The structure of the wall is considered as known and the identification procedure estimates either the thermal conductivity or the thickness of the insulation layer. It is therefore a situation of control of the insulation. It shows that a satisfactory estimation could be reached for an analysis duration of one day. This prospective work could lead to the integration of infrared thermography into standard diagnosis procedures.